Effects of Estradiol and Methoxychlor on Leydig Cell Regeneration in the Adult Rat Testis - Chen, Bingbing (Molecular Diversity Preservation International (MDPI), 2014)
The objective of the present study is to determine whether methoxychlor (MXC) exposure in adulthood affects rat Leydig cell regeneration and to compare its effects with estradiol (E2). Adult 90-day-old male Sprague-Dawley rats received ethane dimethane sulfonate (EDS) to eliminate the adult Leydig cell population. Subsequently, rats were randomly assigned to four groups and gavaged with corn oil (control), 0.25 mg/kg E2 and 10 or 100 mg/kg MXC daily from days 5 to 30 post-EDS treatment. The results showed that MXC and E2 reduced serum testosterone levels on day 58 post-EDS treatment. qPCR showed Hsd17b3 mRNA levels were downregulated 7–15 fold by E2 and MXC, indicating that development of the new population of Leydig cells was arrested at the earlier stage. This observation was supported by the results of histochemical staining, which demonstrated that Leydig cells in MXC-treated testis on day 58 post-EDS treatment were mostly progenitor Leydig cells. However, Pdgfb mRNA levels were downregulated, while Lif transcript levels were increased by MXC. In contrast, E2 did not affect gene expression for these growth factors. In conclusion, our findings indicated that both MXC and E2 delayed rat Leydig cell regeneration in the EDS-treated model, presumably acting by different mechanisms.